Clarissa Harlowe; or the history of a young lady $1 (BVolume 8s - Richardson, Samuel, 1689-1761 (Salt Lake City, UT : Project Gutenberg, 2004)
"Clarissa Harlowe; or the History of a Young Lady $1 (BVolume 8" by Samuel Richardson is a novel likely written in the early 18th century. This volume continues the tumultuous story of Clarissa Harlowe, a young woman of remarkable virtue and strength, as she navigates the profound trials and tribulations imposed by her family and her tormented relationship with the libertine, Mr. Lovelace. The unfolding narrative portrays Clarissa's resolute character amid external pressures and personal turmoil. At the start of this volume, we see a series of letters indicating escalating tensions between Clarissa and her family members who reproach her for perceived transgressions. The correspondences highlight Clarissa's deteriorating health and her desperate predicament, revealing her reflections on her choices and the unyielding nature of her familial relationships. Meanwhile, Lovelace's mindset teeters between regret and manipulation, as he yearns for Clarissa's forgiveness while also plotting ways to win her back. The opening establishes a dramatic atmosphere filled with emotional depth and conflict, setting the stage for a poignant exploration of love, honor, and societal expectations. (This is an automatically generated summary.)s
Release date is 2004-04-01
Produced by Julie C. Sparks and David Widger
Keywords: England -- Fiction; Psychological fiction; Epistolary fiction; Conflict of generations -- Fiction; Kidnapping victims -- Fiction; Young women -- Crimes against -- Fiction; Rape victims -- Fiction